Traditional Ethics in the Use of AI for Arabic Language Education: An Aristotelian Philosophy Perspective - Bagus Ranu Wijaya; Suja'i Suja'i; Solikhatul Munawaroh (Journal of Islamic Education Thought and Development, 2025)
This research explores the application of Aristotle's ethical principles in the use of artificial intelligence (AI) for Arabic language education. Using a qualitative approach, data were collected through a hermeneutic analysis of Aristotle's philosophical texts and a documentary study of the implementation of AI in Arabic language learning. The findings show that although AI can enhance the effectiveness of Arabic language teaching, it also presents challenges such as dehumanization, digital divide, and over-reliance on technology, from Aristotle's ethical perspective, these challenges highlight the importance of carefully considering the ultimate goal of education. Applying the principles of virtue ethics, this study proposes that AI should be designed not only to transmit knowledge, but also to cultivate students' character and virtues. The concept of phronēsis (practical wisdom) is introduced as an ethical foundation for determining appropriate boundaries in the use of AI, encouraging educators to consider the context and specific needs of learners when integrating technology. This research offers theoretical and practical insights into how traditional values in Arabic language education can be harmonized with modern technological tools to achieve eudaimonia, a state of holistic well-being for learners.